Prevalência de lesões oculares decorrentes de trauma envolvendo a maxila e/ou complexo zigomaticomaxilar - Ribeiro Neto, Claudio Nunes (2009)
Ocular trauma is a relatively frequent condition in Urgency and Emergency Services, being many times associated to facial skeleton fractures. This study aims to evaluate the prevalence of ocular lesions in patient victims of facial trauma involving maxilla or zygomaticomaxillary complex. This is a prospective, cross-sectional study, composed of facial trauma victims subjects admitted to an Oral and Maxillofacial Surgery Service of Emergency and Trauma Hospital - Senador Humberto Lucena (João Pessoa - PB), from may to october 2009. The sample consisted of 100 patients. The mean age was 32,54 years. The most common etiology of trauma was motorcycle accident (41%), followed by physical aggression (14%). The most commom type of fracture was zygomaticomaxillary complex fracture, 26 patients in group 1 and 20 in group 2 and the prevalence of maxillary fractures was Le fort I in 8, Le Fort II in 4 and Le Fort III in 10 patients. Presence of fracture and concomintant ocular lesion represented 83% of all patients with ocular lesion. Subconjunctival hemorrhage was the most common lesion (43%), followed by Lack of the pupillary reflex (5%), reduction visual acuity (5%) and diplopia (2%). Facial trauma involving maxilla and zygomaticomaxillary complex associated to fractures of these structures increases the prevalence of ocular lesion.